Testimonies of Vittoria, Lea and Rachele Levi and of Mrs. Montuoro (Balthazar, 2021)
Testimonies of Vittoria Levi in Veniselli, of Lea and Rachele Levi, born in Rhodes and deported to Auschwitz, Willistadt, Theresienstadt, and of Mrs Montuoro deported to Ravensbrück.